Quality assurance and e-learning: blue skies and pragmatism - Ron Oliver (Association for Learning Technology, 2005)
This paper considers the role of quality assurance in e-learning; reflecting on the conditions necessary for successful e-learning. It reviews some of the current international work on quality assurance in this area and goes on to consider the ways in which the quality of a process or activity can be assessed–focusing on the use of benchmarking and specification of standards.